Scientific and technological vocations: Identity for Latin America from the south-southeast of Mexico - Jiménez-León, Rodolfo (Emerging Trends in Education, 2022)
The new social identities within educational spaces, generate a call for new knowledge to address them from models that allow the visibility of the innovations produced in educational organizations in the third stage of the 21st century. The study addresses the elements that contribute to the formation of scientific and technological vocations in young people from non-educational areas, allowing to identify models according to reality. With the experimentalism of the combined design, it is answered: (1) How is the strengthening of student identity by scientific vocations influenced from the participation in events? (2) What is the relationship between identity, symbol and event in the school culture? Through the qualitative approach with narrative interaction are defined the dimensions of (1) educational context, (2) identity, and (3) symbols of the South-Southeast of Mexico. This Is achieved from the interpretive phenomenological paradigm with the participation of students, teachers and communities of experts with the support of grounded theory. The document provides a descriptive methodological framework and the review of international qualitative studies on methodological techniques. Likewise, it proposes lines of action for the development of effective schools and strong organizational cultures for the management of the institutional image in the areas of identity and communication. Keywords: Scientific culture; Social identity; Educational management; Social sciences; Educational policy.